Semi-analytical analysis of the interwire multi-state contact behavior of a three-layered wire rope strand. (1st October 2020) - Chen, Yuanpei; Tan, Hong; Qin, Wei
Graphical abstract: Highlights: The multi-state contact property of a three-layered wire rope strand is analyzed. There is a coupling interaction between the contacts of different forms. All of the contact regions expand with the increasing lay angles of helical layers. The severest contact occurs between the middle and outer layers. Abstract: In this paper, the interwire multi-state contact behavior of a three-layered wire rope strand is studied with consideration of the radial squeeze between all of the layers and the coupling relationship between the contacts of different forms. Based on the elastic thin rod theory of Love and the contact mechanics, a coupling mathematical model is established for the multi-state contact property and the static mechanical behavior of the strand subjected to axial loads. Then the model is solved with a coupling solution scheme in which a semi-analytical method is applied in order to determine the fast solution of the nonlinear contact problem. The results show that as the lay angles of different layers increase, both the helical banded line contact region between the core and middle layers and the discrete elliptical point contact region between the middle and outer layers become larger. Additionally, most of the contact pressures, contact deformations, and internal stresses of the wires in all of the layers increase. The contact pressures, deformations, and stresses of the wires due to the contact between the middle and outer layers are larger than those between the core layer and the middle layer are. The large lay angle of the middle layer and the small lay angle of the outer layer help to balance the contact performance between the contacts of different forms and to prolong of the strand's service life.